Investigation of Suit Ability of Red Onion Juice as PH Indicator in Acid-Base Experiments. - Tumuheirwe, Promise (Kabale University, 2024)
Today synthetic dyes are the choice of acid-base titrimetric analysis, but due to environmental pollution as well as the global crunch, there became a growing need to utilize indigenous natural resources as acid-base indicators in the laboratory due to their environmental friendliness, easy availability, and cheap compared to synthetic standard indicators. Red Onions (Allium cepa) were one of the natural compounds being investigated in this study. In this research project, both quantitative and qualitative methods were employed to bring out unbiased results. Red onions were cut into small pieces, ground to remove the juice, and boiled in 1000cm' of distilled water, filtrated to obtain the red onion juice which was colored purple which changed the blue litmus paper to red and was used as pH indicator for both qualitative and quantitative experiments. Qualitatively, 5-6 cops of red onion juice were added to test tube 1,2,3 containing hydrochloric acid, and sodium hydroxide, and distilled to test the suitability of the red onion juice indicator, the observations made indicated that the pH of the solution in test tube 1,2,3 was 2,8, 13 respectively which implied iat hydrochloric acid was acidic, sodium hydroxide was a base and distilled water was neutral hence qualitatively red onion juice can suitably be used as a PH indicator to test the alkalinity and acidity of the solution. A comparative study of red onion juice indicator with synthetic standard indicators (Methyl Orange and Phenolphthalein Indicators) was carried out to evaluate the efficiency and accuracy of red onion juice indicator as the acid-base indicator. The results obtained from titration of 0.1 M HCl and 0.1 M NaOH using red onion juice indicator were similar to those rilled using Phenolphthalein indicator with a slight difference of 0.64cm3. it was therefore concluded that red onion juice indicator can be used as a substitute for phenolphthalein indicator in aid-base experiments.